Forms of Slow Learner Student Interaction in Elementary Schools - Ganis Rindang Mahesty; Abduh, Muhammad Abduh (Jurnal Elementaria Edukasia, 2024)
This research is motivated by social interactions among slow-learner students in elementary schools. The intellectual capacity of slow learner students is low, and the affective aspects of these students in their relationships or social interactions are also hampered. So this research aims to explore information about the forms of social interaction among slow learner students in class III, SD N Krikilan 1, Kalijambe sub-district. The approach used in this research is a qualitative approach with a case study method. Extended observation techniques and source triangulation are the techniques used to validate the data in this research. Research results are analyzed using data analysis in the form of data reduction, data presentation, and conclusion. The results of the research show the forms of social interaction between individuals, such as how to behave, self-courage in the environment, self-adjustment, facing criticism and failure, and self-confidence. Individual social interactions with groups look like how they take responsibility, play roles in groups, and show themselves in front of other people. Group social interaction with groups includes collaborating with the environment, social attitudes, and cognitive abilities.